Comparison of regenerative potential of petals, stamens and pistils of five Sedum species in vitro - Wojciechowicz, Maria K. (Biodiversity: Research and Conservation, 2007)
The regeneration potential of different explants from flower buds (petals, stamen and pistils) was studied in Sedum acre, S. aizoon, S. floriferum, S. gracile and S. spectabile. The effects of MS medium, supplemented with nine PGR combinations of 6-benzylaminopurine (BAP 1.0-3.0 mg l-1) and indole-3-butyric acid (IBA 0.1-1.5 mg l-1) on regeneration, were compared. Regenerated plants were obtained in cultures of petal, stamen and pistil in all studies species. Three-way analysis of variance allowed to assess the effect of medium composition, explant type and genotype on regeneration potential, expressed as the percentage of regenerating explants and the average number of shoots produced from the explants. All analysed factors significantly affected the regeneration process. PGR composition had the most significant effect on the average number of produced shoots. MS medium containing 3.0 mg/l BAP and 1.0 mg/l IBA proved to be optimal for plant regeneration in Sedum. Explant type had the most significant effect on the percentage of regenerating explants. For petals the percentage of regenerating explants (40%) was nearly twice as high as in other explant types. Genotype had the most significant effect on the average number of regenerated shoots. The highest number of regenerated shoots per explant (3.25) was recorded in S. floriferum.